2022
DOI: 10.1038/s41598-022-16022-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure to MoO3-NP and common bean fertilized by MoO3-NPs on biochemical, hematological, and histopathological parameters in rats

Abstract: Nanotechnologies has been used to introduce several beneficial tools in the agricultural field. Herein, the effect of molybdenum oxide nanoparticles (MoO3-NPs) was investigated by evaluating the hematological, biochemical, and histopathological parameters in rats orally exposed to MoO3-NPs or fed common beans (CB) fertilized by MoO3-NPs. In the first study, 18 rats were randomly divided into 3 groups: G1 (control group) was given water orally, while G2 and G3 were administered 10 and 40 ppm MoO3-NPs by oral ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Moreover, Shaban et al studied the effect of plants fertilized by nano-fertilizer on the rats' health. They found that the common bean fertilized either by ZnO 76 or by MoO 3 -NPs 77 does not cause any harm to rats that feed on it.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Shaban et al studied the effect of plants fertilized by nano-fertilizer on the rats' health. They found that the common bean fertilized either by ZnO 76 or by MoO 3 -NPs 77 does not cause any harm to rats that feed on it.…”
Section: Discussionmentioning
confidence: 99%
“…These results raise concerns about possible negative physiological effects of ZnONP-treated WKB and call for more research into the safety of nanomaterials used in food production. In summary, the use of nanotechnologies in agriculture has produced useful tools, but another study’s emphasis on molybdenum oxide nanoparticles (MoO 3 NPs) raises several crucial questions [ 173 ]. Different results were seen in rats orally exposed to MoO 3 NPs and MoO 3 NPs-fertilized common beans (CB) via hematological, biochemical, and histopathological analyses.…”
Section: Applications Of Nanomaterials In Biocontrol and Plant Growth...mentioning
confidence: 99%
“…It is, therefore, not difficult to notice the serious health risks of NPs. The influence of titanium dioxide (TiO 2 ) NPs on the viability and proliferation of mouse Leydig cells; reduction in sperm motility in the presence of Au-NPs; inhibition of postimplantation development of mouse embryos by quantum dots from Cd and Se core; toxicity to the stem of mouse spermatogonia by Ag-NPs, Al-NPs, Mo-NPs; and inhibition of embryo differentiation mouse stem cells by silica NPs were all confirmed [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 96%